Ethnomathematics Exploration of West Tulang Bawang Tikew Woven - Novellia Hendriawati; Fitria Lestari; Noprisa Noprisa (Kognitif: Jurnal Riset HOTS Pendidikan Matematika, 2026)
This study explores ethnomathematical elements embedded in Tikew weaving, a traditional craft of the Lampung culture. To date, no ethnomathematics research has specifically examined Tikew weaving in West Tulang Bawang, indicating a gap in the literature regarding the mathematical and cultural values inherent in this local practice. Therefore, this study aims to identify mathematical concepts from an ethnomathematical perspective and to examine the cultural values reflected in Tikew weaving. This research employed a qualitative ethnographic approach using a multidisciplinary perspective. Data were collected through observations, interviews, and documentation. The research instruments consisted of interview guidelines and observation protocols. Data analysis was conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The findings reveal that Tikew weaving reflects Lampung cultural values while simultaneously exhibiting meaningful mathematical patterns, particularly geometric concepts. These concepts include plane geometry and three-dimensional forms manifested in the structural patterns of Tikew woven products. The results demonstrate that Tikew weaving can serve as a rich source of contextual mathematical ideas grounded in local culture. This study contributes to the enrichment of ethnomathematics literature by documenting mathematical concepts rooted in indigenous cultural practices. In addition, it supports cultural preservation and offers alternative instructional media for mathematics learning based on local culture. By integrating local cultural contexts, mathematics learning can become more meaningful, contextual, and engaging, while also fostering students’ appreciation of cultural heritage.